Progress towards generation of human haematopoietic stem cells - Wahlster, Lara; Daley, George Q. (Nature cell biology, 2016)
De novo generation of haematopoietic stem cells from different human pluripotent stem cell sources remains a high priority for haematology and regenerative medicine. At present, efficient derivation of functional haematopoietic stem cells with the capability for definitive in vivo engraftment and multi-lineage potential remains challenging. Here, we discuss recent progress and strategies to overcome obstacles that have thwarted past efforts. In addition, we review promising advances in the generation of mature blood lineages and the potential of induced pluripotent stem cells.